Элементы здоровьесберегающих технологий на занятиях по астрономии - Телегина, О.С.; Омарова, Ж.М. (My University, 2013)
This article is devoted to a question of use of health saving technologies in higher education institution. Considered some receptions promoting creation of the active and at the same time comfortable atmosphere on different types of classes in astronomy for students of the specialty «Physics»